Making sense of Malay sexuality: An exploration - Shamsul A.B.,; Mohamad Fauzi Bin Sukimi, (Universiti Kebangsaan Malaysia, 2006)
This article is a three-part exploratory study of Malay sexuality. Part one provides an insight into the epistemological and ontological aspects of sexuality and gender; part two looks at the case of Anwar Ibrahim as one that illuminates the ways in which Malay society grapples with issues of sex and morality; and part three interprets the Anwar Ibrahim’s case from the epistemological and ontological perspective of gender and sexuality. The case received much attention locally and abroad because it involved a political leader who had been seen by many as a probable Prime Minister. However, Anwar Ibrahim was alleged to have indulged in unnatural sex with a few men, forbidden in Islam, and shocking to many because of his image as a pious Muslim leader. His case, however, provides an opportunity to analyze relevant wider issues about the construction of Malay sexuality and morality